Anti-Lock Braking System (International Journal of Innovative Research in Engineering & Management, 2023)
The Anti-Lock Braking System (ABS)  is one of the automotive industry safety functions. The  vehicle's braking difficulty is lessened while its strength  is boosted thanks to the installation of this safety system.  Anti-Lock Hydraulic Brake tyre efficiency is improved as  well since the roadway and the tyre are not eroded.  However, this strategy does not work effectively in areas  with bad road conditions. The latest advance known as  the electronic brake power distribution to overcome the  inconvenient automobile industry. "Electronic brake  power distribution" is productive irrespective of whether  street conditions such as frosty, watery, etc. are  unfavourable. It also reduces braking and improves  vehicle stability by incorporating utility in a control unit.  The ABS is used in vehicles to prevent wheel bolting and  slip after braking. The slip percentage shows the speed  and rotation of the vehicle. Mechanized systems that  suddenly require restrictions, rhythm braking that was  boiling by convenient drivers with an earlier brake system  are the subject of this investigation When the driver can  respond more quickly, it's easier to steer. Driving  assistance and distance limit spotting are provided by the  ABS, alternatively on free surfaces such as gravel or  snow secured asphalt, on illusive and dry surfaces. The  anti-lock braking system may completely enhance  braking distance even if vehicle control system is still  improved.
Keywords: Anti-Lock Braking System; ECU; Fuzzy Controller; Neural Network; Vehicle